Influence of Sharia Service Quality, Islamic Values, and Destination Image Toward Loyalty Visitors’ on Great Mosque of Demak - Kasdi, Abdurrohman; Saifudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
The purpose of this study is to examine the influence of sharia service quality, Islamic values and destination image toward loyalty with visitors’ satisfaction as an intervening variable, a study on the great mosque of Demak tourism. This is field research using a quantitative approach. The data used are primary and secondary data taken with survey method. There are three independent variables, namely: (X1) the quality of sharia service, (X2) Islamic values, and (X3) the destination image. The dependent variable (Y1)/loyalty and intervening variable (Y2) are visitor satisfaction. The population of this study is all visitors orpilgrims of the great mosque of Demak in 2018. The sampling technique used is purposive sampling with 167 respondents. The results of this study indicate that: (1) the sharia service quality does not affect the loyalty, (2) the Islamic values have a direct positive and significant effect on the loyalty, (3) destination image has a direct positive and significant effect on loyalty, (4) the sharia service quality has no effect on the visitors’ satisfaction, (5) the Islamic values have no effect on the visitors’ satisfaction (6) the destination image has a direct positive and significant effect on the visitors’ satisfaction, (7) the visitors’ satisfaction has a direct positive and significant effect on the loyalty, (8) the visitors’ satisfaction does not mediate the relationship between the sharia service quality and loyalty (9) the visitors’ satisfaction does not mediate the relationship between the Islamic values and loyalty, and (10) the visitors’ satisfaction mediates part of the relationship between destination image and loyalty.